Development and performance evaluation of a low cost water - wheel for lifting water at low heads - JAYAN P. R; Er. M. R. Sankaranarayanan (Guide) (Tavanur 1992 Kelappaji College of Agricultural Engineering and Technology)
Development and performance evaluation of a low cost water - wheel for lifting water at low heads
Development and performance evaluation of a low cost water - wheel for lifting water at low heads